2000
DOI: 10.1097/00000658-200002000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Helicobacter pylori Prevents Recurrence of Ulcer After Simple Closure of Duodenal Ulcer Perforation

Abstract: Eradication of H. pylori prevents ulcer recurrence in patients with H. pylori-associated perforated duodenal ulcers. Immediate acid-reduction surgery in the presence of generalized peritonitis is unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
3
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(102 citation statements)
references
References 29 publications
7
88
3
4
Order By: Relevance
“…In Europe and the United States, the incidence of duodenal ulcer constitutes a significant percentage compared with the other peptic ulcers and a lot of evidence that recurrence could be inhibited by eradicating duodenal ulcer has been stored [42,43]. However, there was a moment when a question was raised as to whether eradication was truly effective for inhibiting recurrence of gastric ulcer or not [44].…”
Section: Prevention Of Ulcer Recurrencementioning
confidence: 99%
“…In Europe and the United States, the incidence of duodenal ulcer constitutes a significant percentage compared with the other peptic ulcers and a lot of evidence that recurrence could be inhibited by eradicating duodenal ulcer has been stored [42,43]. However, there was a moment when a question was raised as to whether eradication was truly effective for inhibiting recurrence of gastric ulcer or not [44].…”
Section: Prevention Of Ulcer Recurrencementioning
confidence: 99%
“…The exclusive focus on male subjects in this series is a fact not found in other parallel studies or related series, although there is wide predominance of cases in men [1][2][3]6,7 . This can be explained by the short period of data collection associated with greater exposure to risk factors, such as smoking and alcoholism.…”
Section: Results Results Results Resultsmentioning
confidence: 88%
“…But, the effect of H. pylori eradication in complications of this disease, like perforation, is still a matter of research. From the year of 1995 on, several publications demonstrated that the simple closure of perforated ulcers, plus the eradication of H. pylori, diminishes relapse rates significantly, inducing this strategy as treatment for this complication 1,3,7,12,15,16,18,19,20,21,24,28 . Historically, Sebastian, et al 24 were the first to suggest association between H. pylori …”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez-Sanjuan, et al 21 also removed those patients, as they presented with a higher rate of ulcer re-perforation. These authors also contraindicate closure of gastric ulcers of locations other than those, for the relapse rate is too high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation